A concept of integrated environmental approach for building upgrades and new construction: Part 1—setting the stage. (January 2015) - Bomberg, Mark; Gibson, Michael; Zhang, Jian
This article highlights the need for an active role for building physics in the development of near-zero energy buildings while analyzing an example of an integrated system for the upgrade of existing buildings. The science called either Building Physics in Europe or Building Science in North America has so far a passive role in explaining observed failures in construction practice. In its new role, it would be integrating modeling and testing to provide predictive capability, so much needed in the development of near-zero energy buildings. The authors attempt to create a compact package, applicable to different climates with small modifications of some hygrothermal properties of materials. This universal solution is based on a systems approach that is routine for building physics but in contrast to separately conceived sub-systems that are typical for the design of buildings today. One knows that the building structure, energy efficiency, indoor environmental quality, and moisture management all need to be considered to ensure durability of materials and control cost of near-zero energy buildings. These factors must be addressed through contributions of the whole design team. The same approach must be used for the retrofit of buildings. As this integrated design paradigm resulted from demands of sustainable built environment approach, building physics must drop its passive role and improve two critical domains of analysis: (i) linked, real-time hygrothermal and energy models capable of predicting the performance of existing buildings after renovation and (ii) basic methods of indoor environment and moisture management when the exterior of the building cannot be modified.